Reaction of cassava genotypes to the cassava mosaic disease in three distinct agroecologies in Nigeria - Ngeve, J.M.; Nukenine, E.N.; Dixon, Alfred G.O. (Wiley, 2003)
Nine cassava genotypes were grown at six representative sites in Nigeria for 3 years to study their response to cassava mosaic disease (CMD), investigate the influence of genotype × environment (G× E) interactions on their reactions to the disease, and identify genotypes with stability to the disease, using the Additive Main Effects and Multiplicative Interaction statistical model. Environments, genotypes and G × E interactions were highly significant (P < 0.01) for the disease. The G × E interactions accounted for 19.5% of the treatment sums of squares for CMD and influenced the relative ranking of genotypes across environments. The magnitude of the G × E interaction effect for CMD was larger than that of genotypes. Examination of the G × E interaction structure revealed specific areas where screening of cassava genotypes for resistance to CMD could be performed best. The study identified genotypes such as TMS 30001 and 63397 with resistance to CMD and CMD‐stable clone U/41044, which could be distributed to growers, and sites such as Ibadan and Ubiaja with high CMD severity for screening genotypes for reaction to CMD.